2020
DOI: 10.1021/acs.cgd.0c00070
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous FexCo1–x Wire-like Nanostructures Manufactured through Surfactant-Free Magnetic-Field-Induced Synthesis

Abstract: So far, it has been proven that the magnetic-field-induced (MFI) synthesis is a process which mainly leads to the formation of magnetic metallic one-dimensional nanostructures. Taking advantage of this method, the new procedures which allow manufacture of the magnetic bimetallic iron–cobalt wire-like nanochains with Fe0.75Co0.25, Fe0.50Co0.50, and Fe0.25Co0.75 compositions are demonstrated in this work. They were produced through a simple one-step magnetic-field-induced (MFI) chemical co-reduction of three dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 71 publications
1
7
0
Order By: Relevance
“…[11,24,25] So far, it has been proven that the magnetic-field-induced synthesis is a process which mainly leads to the formation of magnetic metallic 1D nanostructures. [27][28][29] For example, Krajewski et al fabricated wirelike amorphous FeCo nanostructures through a simple one-step magnetic-field-induced chemical reduction method. [27] Wang et al fabricated 1D Fe 3 O 4 /C composite microrods via a facile one-pot solvothermal reaction in the presence of an external magnetic field.…”
Section: Electromagnetic (Em) Wave Absorption Materials Have Attractementioning
confidence: 99%
See 1 more Smart Citation
“…[11,24,25] So far, it has been proven that the magnetic-field-induced synthesis is a process which mainly leads to the formation of magnetic metallic 1D nanostructures. [27][28][29] For example, Krajewski et al fabricated wirelike amorphous FeCo nanostructures through a simple one-step magnetic-field-induced chemical reduction method. [27] Wang et al fabricated 1D Fe 3 O 4 /C composite microrods via a facile one-pot solvothermal reaction in the presence of an external magnetic field.…”
Section: Electromagnetic (Em) Wave Absorption Materials Have Attractementioning
confidence: 99%
“…[ 27–29 ] For example, Krajewski et al fabricated wire‐like amorphous FeCo nanostructures through a simple one‐step magnetic‐field‐induced chemical reduction method. [ 27 ] Wang et al fabricated 1D Fe 3 O 4 /C composite microrods via a facile one‐pot solvothermal reaction in the presence of an external magnetic field. [ 29 ] However, the measured EM parameters are related to polymer composites with random distributions of 1D magnetic samples, which somewhat diminish the complex permeability and result in a negative effect on EM wave absorption properties.…”
Section: Introductionmentioning
confidence: 99%
“…Krajewski et al [10] studied a new technology of magnetic field-induced synthesis of magnetic Fe-Co alloy (Fe 0.75 Co 0.25 , Fe 0.50 Co 0.50 and Fe 0.25 Co 0.75 ) linear nanochains (Figure 1), using NaBH 4 aqueous solution as reducing agent, through a simple one-step magnetic fieldinduced chemical cooperative reduction reaction of three different concentrations of Fe 2+ and Co 2+ ion precursor solutions, to prepare the amorphous bimetallic Fe Co linear nanostructures with ideal Fe/CO ratio which have special bimetallic alloy core and very thin oxide shell structure. The Fe-Co alloy material is a ferromagnetic material, and its magnetic properties are related to its structural properties and chemical composition.…”
Section: Metal Nanomaterialsmentioning
confidence: 99%
“…Fig1. SEM images of (a) Fe, (b) Fe0.75Co0.25, (c) Fe0.50Co0.50, (d) Fe0.25Co0.75 wire-like nanostructures, and (e) Co nanoparticles [10] 3 Oxide nanomaterials Li et al [11] used one-step thermal decomposition route to rapidly synthesize octahedral magnetite (Fe 3 O 4 ) nanocrystals. Through adjusting the ratio of precursor to surfactant, the average particle size can be well controlled from 8nm to 430nm.…”
Section: Metal Nanomaterialsmentioning
confidence: 99%
“…The usage of NaBH 4 as the reducing agent in precipitation method usually leads to the formation of nanoparticles [ 3 , 9 , 10 , 11 , 12 , 13 ]. However, it has been recently demonstrated that the presence of an external magnetic field during the synthesis of iron and/or cobalt nanoparticles can cause their alignment and results in the formation of iron, cobalt or iron–cobalt Wire-like nanostructures [ 14 , 15 , 16 , 17 ]. Their morphologies and structural properties are very specific because they look like long chains of nanoparticles.…”
Section: Introductionmentioning
confidence: 99%